Determinants of Firms’ Innovation Activities: A Case Study of German Knowledge-Intensive Industries - Hájek, Petr; Stejskal, Jan; Prokop, Viktor (East Asia Research Universiti Malaysia, 2017)
Business innovation environment varies across countries and industries. Various determinants should therefore be studied in both sectoral and national context. This enables to find effective instruments that promote firm innovation activities. Most importantly, these determinants should be examined in innovation leader countries. For the same reason, knowledge-intensive industries have attracted increasing attention. Germany is one of the most innovative economies in the world and, in addition, it is the largest economy in the European Union. Therefore, we aim to analyze determinants of innovation activities in knowledge-intensive industries in Germany. We use truncated regression models to show that, in contrast to knowledge-intensive business services, university knowledge spillovers are critical for the innovation performance of German knowledge-intensive manufacturing industries. Our findings provide (1) an initial analysis of innovation activity in German knowledge-intensive industries and (2) practical implications and recommendations for policy makers.
Determinanty inovačních aktivity firem: případová studie německých znalostně intenzivních firem
Keywords: innovation activities; case study; Germany; knowledge-intensive industries.; inovační aktivity; případová studie; Německo; znalostně intenzivní průmysl